THE EFFECT OF INTERNAL AUDIT SYSTEM AND IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE ON FRAUD - Cindy Triningsih; Mustapa Khamal Rokan; Muhammad Lathief Ilhamy Nasution (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2023)
The purpose of this study was to determine the effect of the internal audit system and the application of good corporate governance on fraud at Indonesian Islamic banks (BSI). This study collected data and information by sending questionnaires to 97 people who work at Bank Syariah Indonesia (BSI) in Rantau Parapet, North Sumatra. The analysis technique uses multiple regression by testing the hypothesis t test and F test. The results show that the significance value of the internal audit system variable is 0.035 <0.05, which means that the internal audit system variable has a significant influence on fraud, the significance value of the good implementation variable corporate governance of 0.035 <0.05, which means that the variable implementation of good corporate governance has a significant influence on fraud (Fraud). Then simultaneous testing shows the result that the significant value of F is 0.000 <0.05 which means that simultaneously the internal audit system and good corporate governance have an effect on fraud. The conclusion is that both partially and simultaneously the internal audit system variables and good corporate governance have an effect on fraud.